Interplay of ion-conduction and nanoscale self-assembly in amphiphilic Janus-Type hexa-peri-hexabenzocoronenes - Weigold, Svenja; Spyridakou, Marianna; Tzourtzouklis, Ioannis; Freudenberg, Jan; Bunz, Uwe H. F.; Müllen, Klaus; Floudas, George (ACS applied nano materials, 2024)
Ionic discotic liquid crystals combine ion conduction with fluid, yet ordered, liquid crystal phases at ambient temperature, making them suitable nanomaterials for ion transport and energy storage. A series of Janus-type hexa-peri-hexabenzocoronenes (HBCs) with ionic (sulfonate) groups covalently bonded to the HBC core, and tetraalkylammonium counterions (sizes from 0.15 to 0.95 nm) are synthesized and investigated with respect to the self-assembly and ion dynamics. We find that the counterion size affects the nanoscale self-assembly and ionic conductivity in opposite ways. Smaller counterions act as structure formers, whereas larger ones act as structure breakers. The latter exhibits the highest ion dc-conductivity. We quantify the effect of Coulomb interactions on the self-assembly, the glass temperature Tg (which was found to vary by 30 K), and the dc-conductivity (varying by 4 orders of magnitude). The precise synthesis of tailor-made ionic discotic liquid crystals with the HBC core and the characterization of their physical properties revealed that ion-conduction and nanoscale self-assembly in HBCs can be modulated by tuning electrostatic interactions, e.g., by adjusting the size of counterions.